Book review: Anand, N. 2017: Hydraulic City: Water and the Infrastructures of Citizenship in Mumbai. (April 2019) - Shah, Sameer H.
Anand, N. 2017: Hydraulic City: Water and the Infrastructures of Citizenship in Mumbai . Durham and London: Duke University Press. 312 pp. US$99.95 (Cloth), US$26.95 (Paper). ISBN: 978-0-8223-6254-8 (Cloth), 978-0-8223-6269-2 (Paper).